PEMELIHARAAN SHUTDOWN MEASUREMENT PADA PERALATAN CURRENT TRANSFORMATOR DAN LIGHTNING ARRESTER PADA BAY LINE KUTA 2 GARDU INDUK 150kV SENGKOL. - aiza_22; Ariessaputra, Suthami (Depertment of Electrical Engineering University of Mataram, 2024)
This research aims to find out how and the results of routine 2-year maintenance on current transformers and Lighting Arrester in a state of blackout (shutdown measurement). Tests carried out in the form of testing insulation resistance and grounding resistance. The measuring instrument used in testing insulation resistance, namely Megger MIT 1025 while for testing grounding resistance used Digital Earth Kyoritsu Model 4105A. The results obtained in the insulation resistance test are good with a predetermined standard of 1Mohm per 1kV on the current transformer while on the Lightning Arrester with a predetermined standard of > 1Gohm obtained good results as well so it is feasible to operate. The results of the grounding resistance test on the current transformer are in good condition with a standard of <1Ohm, the test results obtained are also good on lightning arresters with the same standard <1Ohm so that this equipment is suitable for operation